PERLINDUNGAN HUKUM DAN PENGUPAHAN BAGI TENAGAKERJA PEREMPUAN - Hartati, Margaret (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Legal protection for women workers is a right and obligation of the state. Labor for women is still in the spotlight of society, the lack of guarantees for the health and safety of the womb for female workers is one of the factors causing various problems in the field of labor. The large number of female workers in companies still receives bad treatment from employers such as discrimination, violence, and is considered weak physically and mentally, while women's wages are smaller than men's. The method used is juridical normative or library law research, the purpose of this study is to describe the implementation of women workers to see legal protection of decency and security, justice, health and rights for women workers.